Analysis of concrete columns with high-performance concrete jackets and polymer wraps. Issue 8 (14th August 2022) - Algburi, Atheer; Sheikh, M. Neaz; Hadi, Muhammad
Abstract : Cross-sectional analyses of circular and square reinforced concrete (RC) columns strengthened with reactive powder concrete jacketing and fibre-reinforced polymer (FRP) wrapping were undertaken. The stress block method was used to determine theoretical axial load–bending moment (AL–BM) interactions of the columns. These were then compared with experimental results and found to be in very good agreement. A parametric study was also undertaken to investigate the most important factors that influence the AL–BM capacity of circular and square strengthened columns. Finally, a group of theoretical AL–BM interactions for circular and square strengthened columns was produced. These can be used in a wide range of applications for strengthening RC columns with high-performance concrete jackets and FRP wraps.